Work ability, age and intention to leave aged care work - Austen, Siobhan; Jefferson, Therese; Lewin, Gill; Ong, Rachel; Sharp, R. (Blackwell Publishing, 2015)
Aim: To describe the work ability of mature age women workers in Australia's aged care sector, and to explore the relationship between ageing, work ability and intention to leave. Method: Logistic regression techniques were applied to a sample of 2721 responses to a survey of mature age women workers in the aged care sector. Results: Mature age women working in the Australian aged care sector have relatively high levels of work ability by international standards. Furthermore, their work ability remains high in their 50s and 60s, in contrast to some prevailing stereotypes. However, work ability is a key determinant of intention to leave in key occupational groups. Conclusion: Our findings challenge some prevailing stereotypes about the work ability of mature age workers. However, they lend support for the development of retention strategies, which incorporate programs that target low work ability.